Disappointment for Kansas GED® Students Transitioning to PostsecondaryThe Black Hole of Developmental Education - Jeff Zacharakis (Adult Education Research Conference, 2015)
This research uses national and state studies to inform quantitative analysis of adult education students who successfully transition into a postsecondary program. The complexity of this issue precludes making simple causal relations between GEDs enrolling in developmental education courses and successfully earning a certificate and degree.
Keywords: adult basic education; GED®; development education; pathways; postsecondary